2017
DOI: 10.1136/bjsports-2016-096794
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for the use of stem cell therapy for tendon disorders: a systematic review

Abstract: IntroductionStem cells have emerged as a new treatment option for tendon disorders. We systematically reviewed the current evidence for stem cell therapy in tendon disorders.MethodsRandomised and non-randomised controlled trials, cohort studies and case series with a minimum of 5 cases were searched in MEDLINE, CENTRAL, EMBASE, CINAHL, PEDro and SPORTDiscus. In addition, we searched grey literature databases and trial registers. Only human studies were included and no time or language restrictions were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 66 publications
0
43
0
Order By: Relevance
“…In addition, several experimental studies showed that AD MSCs prevented progression of tendon degeneration , increased the tensile strength and type I collagen in tendon repair , decreased fatty infiltration of muscle after repair , decreased tendon defects in human lateral epicondylosis , and reduced the re‐injury rate in race horses . While a recent systematic review reported no evidence for the use of stem cell therapy for tendon disorders currently , all of the two studies for rotator cuff tear in this review actually did not use MSCs, but use bone marrow mononuclear cells between which there should be a huge gap. We find no clinical trial using injection of AD MSCs for rotator cuff disease in the literature so far.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, several experimental studies showed that AD MSCs prevented progression of tendon degeneration , increased the tensile strength and type I collagen in tendon repair , decreased fatty infiltration of muscle after repair , decreased tendon defects in human lateral epicondylosis , and reduced the re‐injury rate in race horses . While a recent systematic review reported no evidence for the use of stem cell therapy for tendon disorders currently , all of the two studies for rotator cuff tear in this review actually did not use MSCs, but use bone marrow mononuclear cells between which there should be a huge gap. We find no clinical trial using injection of AD MSCs for rotator cuff disease in the literature so far.…”
Section: Discussionmentioning
confidence: 88%
“…Preclinical studies for tissue‐engineered repair of cartilage and bone have been quite promising, but most clinical procedures either lack controls or have shown long‐term results that are equivocal to standard‐of‐care . Similarly, stem cell therapies have shown significant promise in controlled preclinical animal studies, but have not shown consistent clinical efficacy in prospective and randomized trials …”
Section: Stem Cell Research and Therapy In Orthopedicsmentioning
confidence: 99%
“…17,18 Similarly, stem cell therapies have shown significant promise in controlled preclinical animal studies, [19][20][21] but have not shown consistent clinical efficacy in prospective and randomized trials. [22][23][24] Despite the lack of clear evidence to support these "stem cell" therapies, numerous clinics continue to offer unproven procedures in the United States, with an unknown number of such clinics outside the United States offering various cell therapies as medical tourism. Not only do many of these procedures not involve actual stem cells, there have been a number of serious adverse effects that have been documented due to unproven stem cell therapies, 25 including growth of a mucus-producing nose in the spine, 26 tumor formation, 27 blindness, 28 and infection.…”
Section: Stem Cell Research and Therapy In Orthopedicsmentioning
confidence: 99%
“…Preclinical research supports the efficacy of MSC in tendon and articular conditions based on the anti-inflammatory and anti-catabolic effect of these therapies. However, current data derived from clinical research are insufficient to establish specific indications and recommendations [60,61]. In fact, media and direct internet marketing have raised expectations around regenerative sports medicine claiming that MSC therapies accelerate return to play without surgery in elite athletes.…”
Section: Are There Research Evidences For Optimal Decision-making?mentioning
confidence: 99%